Implementasi High Order Thinking Skill dalam Pembelajaran Pendidikan Islam di Sekolah Dasar - Nurul Hidayah; Najwa Nailal Husna (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
Teachers have new challenges in facing Era 5.0, teachers are required to be able to make new breakthroughs in planning active, innovative and interesting learning. As educators in the Society 5.0 era, teachers must have digital skills and think creatively. Educators are also required to have the ability to create innovative and dynamic learning. To carry out innovative and dynamic learning, you can apply a learning approach that can improve critical thinking skills called Higher Order Thinking Skills (HOTS). This article presents techniques that teachers can use to enhance and improve the critical thinking skills of PAI students who can use the Higher Order Thinking Skills (HOTS) approach in their learning. To find out the results of implementing the HOTS approach, an evaluation of the research implementation will be carried out. When implementing PAI learning, it is divided into 3 parts based on observations obtained through the HOTS method, namely. The first part is that the teacher makes an analysis of the teaching methods used, and from these results it can be concluded that the class is able to solve problems, for example in the subject of disciplinary behavior. The next step is for the teacher to evaluate the application of the methods used in the teaching and learning process, for example the PAI teacher's negative statements which must be corrected by the students, then the students explain their ideas and contributions. for statements, for example, the material on Disciplinary Attitude and Competitive Attitude is good. In the final stage, the teacher prepares a manifesto to see changes in student behavior in elementary schools (SD) after receiving PAI lessons. In Islamic Religion subjects, what are the obstacles to learning Higher Order Thinking Skills (HOTS) in Islamic Religionsubjects, how is the assessment of Higher Order Thinking Skills (HOTS) learning in Islamic Religion subjects in elementary schools. Guru mempunyai tantangan baru dalam menghadapi Era 5.0, guru dituntut untuk mampu melakukan terobosan-terobosan baru dalam merencanakan pembelajaran yang aktif, inovatif dan menarik. Sebagai pendidik di era Society 5.0, guru harus memiliki keterampilan digital dan berpikir kreatif. Pendidik juga dituntut memiliki kemampuan menciptakan pembelajaran yang inovatif dan dinamis. Untuk melaksanakan pembelajaran yang inovatif dan dinamis, Anda dapat menerapkan pendekatan pembelajaran yang dapat meningkatkan keterampilan berpikir kritis yang disebut Higher Order Thinking Skills (HOTS). Artikel ini menyajikan teknik yang dapat digunakan guru untuk meningkatkan dan meningkatkan kemampuan berpikir kritis siswa PAI yang dapat menggunakan pendekatan Higher Order Thinking Skills (HOTS) dalam pembelajarannya. Untuk mengetahui hasil penerapan pendekatan HOTS maka akan dilakukan evaluasi pelaksanaan penelitian. Pada saat pelaksanaan pembelajaran PAI dibagi menjadi 3 bagian berdasarkan observasi yang diperoleh melalui metode HOTS yaitu. bagian pertama yaitu guru membuat analisis terhadap metode pengajaran yang digunakan, dan dari hasil tersebut dapat disimpulkan bahwa kelas mampu menyelesaikan masalah, misalnya mata pelajaran perilaku disiplin. Langkah selanjutnya guru mengevaluasi penerapan metode yang digunakan dalam proses belajar mengajar, misalnya pernyataan negatif guru PAI yang harus dikoreksi oleh siswa, kemudian siswa menguraikan ide dan kontribusinya. untuk pernyataan misalnya materi Sikap Disiplin dan Sikap Kompetitif sudah baik. Pada tahap akhir, guru menyiapkan manifesto untuk melihat perubahan perilaku siswa di Sekolah Dasar (SD) setelah menerima pelajaran PAI. Pada mata pelajaran Agama Islam, apa saja hambatan pembelajaran Higher Order Thinking Skills (HOTS) pada mata pelajaran Agama Islam, bagaimana penilaian pembelajaran Higher Order Thinking Skills (HOTS) pada mata pelajaran Agama Islam di Sekolah Dasar.